Ethnobotanical knowledge of medicinal plants from Bukhara Region of Uzbekistan - Makhkamov, Trobjon; Eshonkulov, Alijon; Bussmann, Rainer W; Khojimatov, Olim; Zafar, Muhammad; Ahmad, Mushtaq; Ruzmetov, Umid; Yuldashev, Akramjon; Islomov, Sokhib; Khakimova, Dilabza; Xojimatova, Dilnoza; Ergasheva, Nilufar; et al. (Ethnobotany Research and Applications, 2024)
Background: Plants have long been a vital source for traditional medicine preparations used for livestock and humans, both for preventive and curative purposes. The rural population’s ongoing relationship with their environment has led to the development of distinctive indigenous knowledge regarding the uses of plant resources. It is necessary to document this important information now in existence before it is lost or disappears. Ethnobiological literature on Central Asia is scant, random, limited in scope and fraught with taxonomic inconsistencies. Hence, this study is based on an extant ethnobotanical treatise and aims to represent an integrative knowledge of the medicinal plants of Bukhara region, Uzbekistan. Methods: Ethnobotanical data of Bukhara province were collected through direct observation, field interviews, community interviews, and interviews using open and semi-open structured questions. 249 informants (182 men and 67 women) were chosen at random for ethnobotanical interviews, which covered all of the districts in the Bukhara region. The acquired data was then analyzed using quantitative ethnobotanical measures such as Use Value (UV) and Relative Frequency of Citation (RFC). Results: A total of 84 plant species were found through ethnobotanical research in the Bukhara region; these species were categorized into 72 genera and 39 plant families. The analysis of plants based on their life forms as a result of the surveys showed that herbaceous plants are most commonly used in ethnobotany, constituting 94% of all identified plants. Of the 84 identified species, 48 are natural and 36 are cultivated. The research also found that the primary parts of medicinal plants used are leaves (52.4% or 44 species), stems (32% or 27 species), fruits (31% or 26 species), roots (27% or 24 species), seeds (20% or 17 species), flowers (11% or 9 species), and other parts (bulbs, tubers, bark, raisins, spikes, cotton, seed husks, seed beaks) accounting for 11% (9 species) of usage. With a UV of 0.807, Peganum harmala had the highest value among the studied areas. Cucurbita pepo (0.743), Mentha longifolia (0.727), Ziziphora pedicellata (0.679), Brassica rapa (0.618), Raphanus raphanistrum subsp. sativus (0.574), Allium sativum (0.570), Ferula foetida (0.474), Capparis spinosa (0.422), and Glycyrrhiza glabra (0.414) were some of the other high-use species Conclusion: The local populations residing in the desert regions of Bukhara possess substantial knowledge about medicinal plants. The current study documented 84 medicinal plants that were commonly utilized by local populations for the cure of various diseases. Rosaceae family topped the list with seven genera and nine species. Herbaceous plants were most commonly used, constituting 94% of all identified plants. In plant part use patterns, leaves (52.4% or 44 species) were mostly utilized for making various kinds of remedies. Peganum harmala, Cucurbita pepo and Mentha longifolia were the most important species in the study area. Due to the remoteness of the study area and the lack of modern healthcare facilities, the majority of population is dependent on these medicinal plants. The study presents the first detailed exploration of indigenous ethnomedicinal knowledge from remote desert areas in Bukhara region. The study emphasizes the importance of indigenous ethnomedicinal knowledge as well as the declining interest in gaining traditional knowledge among the younger generation, possibly due to an increase in allelopathic medicinal practices. The documentation of indigenous knowledge is essential for its preservation, sharing of information in the public domain, the invention of novel medicines, and future management for the conservation of threatened flora. Key words: Medicinal plants, Bukhara region, Field survey, Ethnobotanical knowledge. Справочная информация: Растения уже давно являются жизненно важным источником препаратов традиционной медицины, используемых для домашнего скота и человека как в профилактических, так и в лечебных целях. Постоянная связь сельского населения с лесами привела к развитию самобытных знаний коренных народов об использовании растительных ресурсов. Необходимо документировать эту важную информацию, которая уже существует, прежде чем она будет потеряна или исчезнет. Этнобиологическая литература по Центральной Азии скудна, разрозненна, ограничена по объему и полна таксономических противоречий. Таким образом, это исследование основано на существующем этноботаническом трактате и направлено на представление комплексных знаний о лекарственных растениях Бухарской области, Узбекистан. Методы: Для сбора данных использовались метод анкетирования и групповые обсуждения, в основном проводившиеся на местных языках. Для этноботанического исследования, охватившего все районы Бухарской области, случайным образом были выбраны 249 информантов (102 мужчины и 28 женщин). Полученные данные затем были проанализированы с использованием количественных этноботанических показателей, таких как потребительная ценность (UV) и относительная частота цитирования (RFC). Результаты: В результате этноботанических исследований в Бухарской области выявлено 84 вида растений; эти виды были разделены на 72 рода и 39 семейств растений. Анализ растений по их жизненным формам в результате обследований показал, что в этноботанике наиболее часто используются травянистые растения, составляющие 94% всех выявленных растений. Из 84 выявленных видов 48 являются природными и 36 культивируются. В ходе исследования также установлено, что основными частями используемых лекарственных растений являются листья (52,4% или 44 вида), стебли (32% или 27 видов), плоды (31% или 26 видов), корни (27% или 24 вида), семена. (20% или 17 видов), цветки (11% или 9 видов) и другие части (луковицы, клубни, кора, изюм, колосья, хлопчатник, семенная оболочка, семенные клювы) составляют 11% (9 видов) использования. Peganumharmala с УФ 0,807 имела самое высокое значение среди изученных территорий. Cucurbita pepo (0,743), Mentha longifolia (0,727), Ziziphora pedicellata (0,679), Brassica rapa (0,618), Raphanus raphanistrum subsp. sativus (0,574), Allium sativum (0,570), Ferula foetida (0,474), Capparis spinosa (0,422) и солодка голая (0,414) были одними из других широко используемых видов. Заключение: На основании этноботанических данных, собранных в районе исследования, можно сделать следующие научные выводы. Во-первых, пожилые люди составляют почти все население, у которого можно собрать этноботанические данные, и с течением времени возможностей сохранить эти знания становится все меньше (богатый опыт традиционной медицины). Во-вторых, поскольку секреты трав обычно передаются из поколения в поколение, те, кто практикует традиционную медицину, обычно старше и не делятся своими знаниями в полной мере. В-третьих, несмотря на обилие лекарственных растений в этом районе, о них знает недостаточное количество местного населения.